Electroencephalographic investigation of the effect of skill level and social inhibition on simulated handgun shooting - Shelley-Tremblay, J.; Jones, P. R.; Demming, C. E.; Labbe-Coldsmith, E. (Journal of Motor Behavior, 2021)
We examined effects of Social Inhibition (SI), and Skill Level (SL) on simulated handgun shooting performance. Electroencephalogram (EEG) was also recorded in order to measure task-related changes in cortical activity. Participants consisted of Novice (NSL) and Experienced (ESL) shooters who were randomly assigned to shoot while in the presence of an audience (Hi SI) or alone (Low SI). The results revealed that NSL were less accurate than ESL in all conditions as was predicted. Shooting accuracy was predicted by alpha and beta amplitude, indicating different roles for attention and anxiety. Prefrontal alpha amplitude was significantly influenced by SL and SI, with a finding that ES showed RH deactivation while NS showed LH deactivation. Findings are discussed in terms of theories of motor control and SI.